JOURNALISTIC GENRES IN THE MAGAZINE "LESKOVAČKI GLASNIK" IN 1927 AND 1928 ON THE SUBJECT OF WOMEN'S RIGHT TO VOTE - Grgov, Aleksandra (CM: Communication and Media ISSN 2466-541X; 2466-5452 (Online), 2024)
The subject of our research are newspaper articles in the magazine "Leskovački glasnik" in 1927 and 1928 that deal with the issue of women's right to vote. The research starts from the following research questions: "Which journalistic genres were represented in the weekly between the wars of the 20th century when writing about women's political organization?" and "How specific structural-compositional elements of certain media content can serve the purpose of preserving the existing social order?" Qualitative content analysis was used in the paper, and the unit of analysis is the newspaper texts of the magazine "Leskovački glasnik" from 1927 and 1928.                Newspapers, due to their practicality and availability, are means of access to knowledge on which a large number of social activities depend, therefore they can subtly influence the creation of public opinion and our perception of reality. Along with other socialization elements, the media play a significant role in the development of gender roles, but also in the creation and maintenance of gender stereotypes. Knowing the complexity of newspaper expression of different historical periods can help us in understanding the current socio-political reality presented through the prism of the media and be an incentive to fight against gender dichotomy, by researching its roots through the diversity of media expression.
Keywords: newspaper text, genre, Leskovački glasnik, social order, women's suffrage, women's party